Guía de práctica clínica para la prevención y manejo del trastorno hipertensivo del embarazo en el primer nivel de atención - Guevara, Enrique (2025)
Introduction. This article summarizes the clinical practice guideline (CPG) for the prevention and management of hypertensive disorders of pregnancy at the primary care level. Objective. To provide healthcare professionals with evidence-based recommendations to support decision-making in the prevention and management of hypertensive disorders of pregnancy in women at risk of preeclampsia who attend primary care health facilities. Methods. A guideline development group (GDG) was formed, consisting of medical specialists and methodologists, who formulated clinical questions in PICO format. In 2025, systematic searches were conducted in PubMed, CENTRAL, Embase, and LILACS to identify systematic reviews addressing each of the formulated questions; in the absence of such reviews, primary studies were sought. The certainty of the evidence was assessed using the GRADE methodology, which was also used to analyze the evidence and develop the recommendations, good clinical practice points, and flowcharts. The clinical practice guideline (CPG) was approved by Directorial Resolution No. 002-2025-INS/CETS. Results. The CPG addressed four clinical questions related to the prevention and management of hypertensive disorders of pregnancy. Based on these questions, two positive recommendations, one negative recommendation, three good clinical practice points, and two flowcharts were developed. Among the formulated recommendations, it was established that in pregnant women at risk of preeclampsia, it is recommended to administer acetylsalicylic acid for the prevention of preeclampsia. In addition, it is suggested to administer calcium for the prevention of preeclampsia. Likewise, in pregnant women with gestational hypertension or preeclampsia without severe features, it is suggested not to administer antihypertensive drugs. Conclusion. Evidence-based recommendations were issued for the prevention and management of hypertensive disorders of pregnancy at the primary care level.